Formulation of Wangi Pandan Leaves (Pandanus Amaryllifolius Roxb) to smooth, moisturize and repair the skin - Juvita Herdianty; Alfara Derista Felany (Strada Journal of Pharmacy, 2020)
Bodyscrub is one of the products that is the result of rapid technological developments today, bodyscrub scrubs are used to maintain the cleanliness and freshness of body skin, bodyscrub products vary greatly starting from price, packaging color, softness of texture and aroma (Nina Hairiyah, Nuryati, and Fitri Nordiyah, 2022).The aim of using a body scrub is to remove dead skin cells, dirt and open pores so that the skin becomes brighter and whiter. Currently, there are many types of body scrubs circulating in society with various benefits ranging from smoothing the skin to whitening the skin (Hairiyah, N., & Nuryati, 2020) Medicinal plants have traditionally been used to treat many diseases and maintain health in Southeast Asia, many plants are described as having traditional medicinal properties. One of the plants that can be used in cosmetics is fragrant pandan leaves (pandanus amaryllifolius roxb) which is a tropical plant from the pandanaceae family. Pandan leaves can also be called pine leaves. because it resembles a pineapple with long, spiral green leaves. narrow and rope-shaped. Pandan leaves contain phytochemical compounds such as steroids, carbohydrates, phenols, flavones, alkaloids, glycosides, amino acids and many vitamins. The appearance and function of the skin is maintained by an important balance between water. This study aims to formulate and evaluate the physical quality results of pandan wangi leaves powder body scrub cream with emulgator concentrations of 15%, 14% and 13% stearic acid, and 1%, 2% and 3% triethanolamine. Experimental research method to determine variations in the concentration of stearic acid and triethanolamine emulsifiers. Observation of the results of evaluating the physical quality of the preparation includes organoleptic tests, homogeneity, pH, stickiness tests, spreadability tests and emulsion type. The result It can be concluded that the fragrant pandan leaf powder body scrub preparation can moisturize the skin, shows a homogeneous scrub with a semi-solid shape, is light green in color and has a typical pandan smell, has a neutral pH of 7.4 and 7.2 on day 7, the pH value is not appropriate The desired number is 6, this is because the preparation is influenced by the number of emulsifiers used. The more stearic acid, the lower the pH because of the large number of acid groups contained in stearic acid, while the more triethanolamine will cause the pH to be high due to the presence of basic groups contained in triethanolamine. with a spreadability of 5.1 cm and 4.83 cm on day 7. This is because the emulsifier concentration is high and the surfactant concentration is low, so the viscosity is very high so the spreadability is low. and the results of adhesion were 88.33 seconds and 49.33 seconds on day 7, adhesion was influenced by the viscosity of the base. Stickiness is closely related to viscosity.